2010
DOI: 10.1016/j.jnutbio.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan extracts inhibit the in vitro intestinal uptake of long-chain fatty acids and cholesterol and down-regulate genes involved in lipogenesis and lipid transport in rats☆

Abstract: Background-Dietary fiber reduces the intestinal absorption of nutrients and the blood concentrations of cholesterol and triglycerides.Aim-We wished to test the hypothesis that high-viscosity (HV) and low-viscosity preparations of barley and oat β-glucan modify the expression of selected genes of lipid-binding proteins in the intestinal mucosa and reduce the intestinal in vitro uptake of lipids.Methods-Five different β-glucan extracts were separately added to test solutions at concentrations of 0.1-0.5% (wt/wt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 37 publications
3
51
1
Order By: Relevance
“…Our present study showed that all BCAAs, skim milk, casein, and whey markedly downregulated ACC, FAS, SREBP-2, and HMGCR, except HMGCR with skim milk. Although this is the first work to demonstrate an effect of dairy proteins and BCAAs on these genes, we previously demonstrated that the soluble dietary fiber, β-glucan, inhibits the uptake of longchain fatty acids in rat intestinal explants and downregulates FAS, ACC, SREBP-1a and -1c mRNA levels and i-FABP and FATP4 mRNA [43]. The present findings suggest that BCAAs and dairy proteins may also decrease fatty acid and cholesterol synthesis by modulating mRNA transcription of these enzymes.…”
Section: Discussionmentioning
confidence: 91%
“…Our present study showed that all BCAAs, skim milk, casein, and whey markedly downregulated ACC, FAS, SREBP-2, and HMGCR, except HMGCR with skim milk. Although this is the first work to demonstrate an effect of dairy proteins and BCAAs on these genes, we previously demonstrated that the soluble dietary fiber, β-glucan, inhibits the uptake of longchain fatty acids in rat intestinal explants and downregulates FAS, ACC, SREBP-1a and -1c mRNA levels and i-FABP and FATP4 mRNA [43]. The present findings suggest that BCAAs and dairy proteins may also decrease fatty acid and cholesterol synthesis by modulating mRNA transcription of these enzymes.…”
Section: Discussionmentioning
confidence: 91%
“…The studied fiber sources, namely, betaglucans from barley and bran from rice, were selected from among cereals because of their particular hypocholesterolemic properties, the mechanisms of action of which on lipidic pattern are very different. Beta-glucans are water-soluble dietary fibers, having gel-forming properties that cause effects on lipid pattern (Marlett et al, 1994;Drozdowski et al, 2010), whereas rice bran is a water-insoluble fiber with active components having a cholesterol-lowering effect (Qureshi et al, 2000;Wilson et al, 2007). The first result of this trial is that the subjects after the 3-week adaptation period with rice bran-enriched foods experienced significant reductions in blood LDL-cholesterol, total cholesterol, apo A-I, total/HDL-cholesterol and glucose, in agreement with previous large studies ( Keys et al, 1960;Burkitt et al, 1974;Trowell, 1975;Cheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, hepatic low-density lipoprotein (LDL)-cholesterol receptors become upregulated to re-establish hepatic cholesterol stores, thus promoting a decrease of serum LDL cholesterol (Reihner et al, 1990). Moreover, a recent study showed that the reduced intestinal fatty acid uptake observed with beta-glucans is associated with the inhibition of genes regulating intestinal uptake and with synthesis of lipids (Drozdowski et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The increased lipid content in the liver could be attributed to the up-regulation of the mRNA levels of lipogenic genes (such as SREBP-1, PPARγ, FAS, ACCa, FABP, GPDH, G6PD and HMGCR) and to the increased activity of lipogenic enzyme (G6PD) and to the depressed activity of lipolytic enzyme (TLP) and to the down-regulation of the mRNA levels of the lipolytic genes (PPARα and CPT1). A-OKGM, as prebiotics, its effect on lipid metabolism in S. Prenanti is opposite to that in mammals [65,66]. Hence, the underlying mechanism needs to be determined in future studies.…”
Section: Resultsmentioning
confidence: 99%